1990
DOI: 10.1177/096032719002200102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of correlated colour temperature on the perception of interiors and colour discrimination performance

Abstract: A feature of many national lighting standards is the recommendation that lamps with high correlated colour temperatures should not be used at low illuminances. The technical justification for this advice is limited so two experiments have been conducted to explore its validity. In the first experiment, fifteen observers carried out colour discrimination tasks and assessed the lighting of a small room lit to different illuminances using lamps with good colour rendering properties but with different correlated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
145
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 6 publications
4
145
2
2
Order By: Relevance
“…For example, is discrimination of the brighter scene from sequential evaluation of lighting from two different light sources 30 comparable with category rating of their brightness when evaluated separately? 44 These two particular studies disagree in their conclusions as to whether SPD affects brightness and one possible explanation is the differences in the particular procedures employed.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, is discrimination of the brighter scene from sequential evaluation of lighting from two different light sources 30 comparable with category rating of their brightness when evaluated separately? 44 These two particular studies disagree in their conclusions as to whether SPD affects brightness and one possible explanation is the differences in the particular procedures employed.…”
Section: Introductionmentioning
confidence: 96%
“…Consider for example, the studies by Boyce and Cuttle 44 and by Flynn and Spencer, 46 both of which sought ratings of the brightness rather than the spatial brightness of the lighting in test rooms. Boyce and Cuttle 44 included separate ratings of bright and dim along five-point response ranges labelled 'very much so' to 'not at all so' and these were made following instruction to test participants to 'describe the lighting of the room in their own words', a prompt to consider the whole environment. Flynn and Spencer 46 sought rating of brightdim along a seven-point semantic differential scale and their test participants were 'asked to rate the space', again a prompt to consider the whole environment whilst making the evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…These lamps are expected to enhance job performance and efficiency and provide a relaxed and aesthetic environment for customers (Baron et al, 1992;Boyce and Cuttle, 1990;Fleischer et al, 2001;Park and Farr, 2007). Plant-growth fluorescent lamps were used in floral refrigerators, because they were installed by manufacturers.…”
Section: Discussionmentioning
confidence: 99%
“…Kruithof [16] showed the comfortable illuminance zone related to the color temperature of light sources called Kruithof curves. However, many studies [17,18,19] which tested the Kruithof curve showed that people's preference of illuminance and CCT might vary depending upon different environments and purposes and could not be completely explained by the Kruithof curve. Park et al [20] evaluated the impact of varying CCT on personal preferences and productivity and suggested that changeable CCT lightings are better than fixed CCT for occupants in a space.…”
Section: A Measurement Of Color Qualitymentioning
confidence: 99%